(untitled) (American Journal of Business Management, Economics and Banking, 2023)
The research dealt with the growth of the volume of deposits and its impact on bank credit, as the research attention is focused on a sample of private Iraqi banks, and the research problem was to identify the growth of the volume of deposits and its impact on bank credit, and the research sought to achieve a number of cognitive goals based on a main hypothesis, so the research chose (5) banks to collect data and information related to the research and that the research period was (2012-2021) and in order to process the data, many financial and statistical methods were used (linear regression rate of change, and ANOVA analysis) statistical methods have produced a number of results, perhaps the most prominent of which is the presence of the significant impact of bank deposits on bank credit. In the context of discussing the results, the applied research emphasized the interest in the growth of the volume of deposits and its impact on bank credit, perhaps the most prominent of which is the continuous and permanent interest in analyzing deposits through the financial ratios used because of their major role in identifying the rate of change in deposits because of its impact on bank credit.